Synthesis and Antifungal Activities of 5-(o-Hydroxy phenyl)-2-[4'aryl-3'chloro-2'azetidinon-1-yl]-1,3,4-thiadiazole - Shiv K. Gupta; P. K. Sharma; M. Bansal; B. Kumar (E-Journal of Chemistry)
New series of 5-(o-hydroxy phenyl)-2-[4'aryl-3'chloro-2'azetidinon-1-yl]-1,3,4-thiadiazole have been synthesized and the structures of the new compounds were established on the basis of IR, 1H NMR spectral data. In vitro antifungal activity (MIC activity) was evaluated and compared with standard drugs of ketoconazole. Compounds 3c in the series has shown interesting antifungal activity against both C. albicans and A. niger fungus. In the gratifying result, most of the compounds were found to have moderate antifungal activity.